CTS Education: the Discourse of Students from the Technical Building Course of Federal Institute of Rio Grande do Norte - Braga da Silva, Elison Victor (2024)
This study examines the perceptions of a group of students regarding the relationships among the construction industry, society, and the environment. It also explores the implementation of CTS (Science, Technology, and Society) education in the formative process of Building Technicians at Federal Institute of Rio Grande do Norte (IFRN) Mossoró Campus. A pedagogical intervention focused on construction waste management was conducted, during which students produced argumentative texts. These texts were then analyzed using content analysis, supported by textual statistics from the IRAMUTEQ software. The results indicate that students feel the training provided to technicians inadequately addresses the socio-environmental impacts of the construction industry. The intervention stimulated reflection on the significance of the topic for the sustainable development of the construction industry, emphasizing the integration of CTS education into the educational journey of the technicians.